THE COMPARATIVE STUDY OF DOWRY REGULATIONS IN INDONESIA AND MOROCCO LEGISLATIONS - Trigiyatno, Ali (Jurnal Syariah, 2021)
This article compares dowry regulations in Indonesia and Morocco. Bearing in mind that Indonesia and Morocco have different characteristics in dowry matter, the regulations are worth comparing for. As understood in Islamic marriages, dowry is an important obligation and must be fulfilled by the bridegroom for the bride. Normative Islamic teaching advocates for dowry that is simple and reasonable, but in practice, sometimes dowry becomes expensive and difficult to be given, and thus, causing unfavorable effects. In addition, dowry also has the potentials to be subjected to disputes between husband and wife if not regulated by legislation in details. The author uses a comparative study of law guided by a normative approach through library research. The main source is the statutes of two countries. Analysis technique used is content analysis. As a result, it is found that with different backgrounds of fiqh school in Indonesia and Morroco-one being strongly influenced by Shāfi‘ī school and the other is influenced by Mālikī school-have similar rules on dowry. The only significant difference is that the Mālikī School and its legislation in Morocco considers dowry as a marriage pillar. Meanwhile, the Shāfi‘ī school and its legislation in Indonesia, even though the dowry is regarded as compulsory, it does not become a condition or a marriage pillar. Other differences are the definition of dowry, regulation of wife’s luggage, lost dowry, defective dowry, introduction of mithil dowry, regulation of dowry disputes before entering the household, and regulation of furniture disputes other than the wife’s luggage.